1797 N.J. Laws 219-20 - (:unkn) unknown (My University, 1797)
Required the assessor of each town to compare the list of 18-to-45-year-olds in the community to the list of persons enrolled for military duty, and to ensure that everyone 18 and older who was not exempted was keeping the proper arms and fulfilling his militia duties.
Keywords: MILITIAS; REQUIRED POSSESSION